81.3k views
2 votes
Which expression is equivalent to 5(2.47y − 2.03)?

12.35y + 10.15
12.35y − 10.15
12.35y + 2.03
12.35y − 2.03

User Tizz
by
3.9k points

2 Answers

2 votes

Answer:


  • \bf 12.35y-10.15

Explanation:


\sf 5(2.47y - 2.03)

Apply the distributive law:-
\sf a\left(b-c\right)=ab-ac


\sf 5\left(2.47y-2.03\right)


\sf 5* \:2.47y-5*\:2.03

Multiply the numbers:-


\sf 5*\:2.47=


  • \sf 12.35


\sf 5* \:2.03=


  • \sf 10.15


\bf 12.35y-10.15

______________________

Hope it helps!

Have a great day!

User Jayant Varshney
by
4.1k points
6 votes

Answer:

b) 12.35y − 10.15

Explanation:

Given equation,

→ 5(2.47y − 2.03)

The equivalent expression is,

→ 5(2.47y − 2.03)

→ 12.35y − 10.15

Hence, option (b) is correct.

User Alexander Zakusilo
by
4.7k points